Análise do impacto das ofertas públicas iniciais sobre as empresas brasileiras: utilizando indicadores contábeis calculados a partir de evidências empíricas no Brasil - Wardil, Felipe Sacramento (2009)
The economic estabilization that Brazil has achieved in the last years, and the increase of brazilians firms' corporate govemance levei made the brazilian's stock market an option for foreign investors. The economic's global warm made the market develop and become a finance option for brazilians firms. In the period between 2004 and 2007 were reaiized 106 IPOs in Bovespa. Using the period mentioned above, this study has as objective show the impact of IPO on brazilians firms, using multiples calculated with accounting data. The using of accounting data alows the comparison of the previous inicial pubiic offer period with the after period. In this study we have verified that the firms used the publics offers as a way of capitalization, more then 90% of used sample firms made issuance of shares. This fact made it possible a reduction of leverage and an increase of firms net operating results after IPO.